Estudo para revitalização da micro central hidrelétrica de Roncador - Garcia, Ângelo Bruno (2011)
In a meeting realized in September 27th 2010 between Curitiba Campus from UTFPR (Federal Technological University of Paraná) and Bocaiúva do Sul’s city hall, it was signed a term of agreement for the creation of an Environmental Education Center in the city, that includes the implantation of a micro power plant for electricity power generation. This work is about the revitalization of the Micro Hydroelectric Power Plant of Roncador that is off since 1959. The development of this work was based in theoretical and practical studies, including field studies, for estimating and evaluating the hydroelectric potential and the condition of the equipment and existents structures. The reactivation of the micro power plant it will be important to the university, because it will have a didactic power plant for the students analyze the operation of the plant that will increase the quality of education, and for the city, because with the return of its operation, it will generate energy, develop the region and an area that is now completely abandoned will be utilized.